STUDI GEOMORFOLOGI UNTUK KELAYAKAN TEKNIS JALAN RUAS KANDANGAN- BAGANDAH KALIMANTAN SELATAN - Poedjoprajitno, Soemantri (Pusat Survei Geologi, 2008)
Kandangan-Bagandah road is the shorthest road alternative, which connects many town in South Kalimantan with the sea port of Batulicin, South Kalimantan.The road crossing a steep slope terrain and the very thick weathered soil has caused this road segment have the high susceptibility of mass movement.Geomorphological problems causing the road damage relate to the condition of landform such as: slope, degree of land density, peat or clay zone. Based on the physical aspect, the problems occurr as: mass movement soil creep, rock fall, development of valley (lateral erosion, backward erosion) and subsidence.Keywords: landform, lineament, sloping, mass movement, roadway